Proyecto ecoturístico como estrategia de conservación de la biodiversidad en fauna y flora de La Reserva Natural de Aves Reinita Cielo Azul y el entorno histórico-cultural. (2021)
In this work, the relationship between tourism and the environment is found, where the conservation of natural, historical and cultural resources of the environment is understood .